Fruit development and capsaicin content of hot pepper (Capsicum annuum) plant cultivated in different soil salinity stress - PURIN CANDRA PURNAMA; ISSIREP SUMARDI; L. HARTANTO NUGROHO (Nusantara Bioscience, 2022)
Abstract. Purnama PC, Sumardi I, Nugroho LH. 2022. Fruit development and capsaicin content of hot pepper (Capsicum annuum) plant cultivated in different soil salinity stress. Nusantara Bioscience 14: 166-171. Land scarcity for cropping at Java Island is a challenge for scientists to look for alternative cropping land. The use of saline land for cropping needs to have further discussed. Red pepper (Capsicum annuum L.) can be used as a plant model because, aside from being used as a vegetable, it is also used as natural medicine because of its secondary metabolite, capsaicin. A harsh environment could induce changes in the primary metabolism, which leads to secondary metabolite decomposition. For example, plants respond to stress, such as salt stress, by synthesizing flavonoids and phenolic acid as defense systems to reduce damage. However, the total sugar level and organic acids are decreased. This research aimed to study the fruit development and capsaicin content of hot pepper grown on various coastal soil sand to know whether or not different growth medium affects the size of each part of the fruit. The design of this research was a Completely Randomized Block Design (CRBD). In this research, five different salinity mediums were used, they were A. 15.20 dS/m, B. 5.70 dS/m, C.1.10 dS/m, and D. 2.85 dS/m obtained from Pandansimo and E. 3.25 dS/m obtained from Sleman, Yogyakarta, Indonesia, as comparation. Seedlings were transferred to the polybag after having four truly expanded leaves. Fruit development was observed every week, starting from the first day after flowering (DAF) to 35 DAF. Pericarpium and placenta thickness, fruit diameter, number, length, and width of the giant cell were recorded appropriately from the slides prepared using the paraffin method. Capsaicin content was determined at 14 and 35 DAF, performed with Gas Chromatography-Mass Spectrometry (GC-MS). The results show structural changes in the exocarpium; on the first day after flowering, there was only one layer of epidermis cells, but at 7 DAF, there was one layer of epidermis cells and one layer of collenchyma cells. Next, at 14 DAF, one layer of epidermis cells and two layers of collenchyma cells are observed. The structure of the mesocarpium, endocarpium, and placenta were not changed. The capsaicin content of the green fruit (14 DAF) was lower than the mature one (35 DAF) in all survival mediums. The highest capsaicin content at 14 and 35 DAF was obtained from a plant grown at medium C. Different growing mediums affected pericarpium and placenta thickness, number, length, and width of the giant cell fruit diameter.